Intravenous lacosamide for acute repetitive seizures and convulsive status epilepticus in critically ill children - Man‐Ru Hsiao; Tzu‐Cheng Tsai; Shao‐Hsuan Hsia; Oi‐Wa Chan; En‐Pei Lee; Jainn‐Jim Lin; Kuang‐Lin Lin (Epilepsia Open)
Abstract Objective Acute repetitive seizures and convulsive status epilepticus are common neurological emergencies in critically ill children. The aim of the study was to evaluate the effectiveness and safety of intravenous lacosamide in critically ill children with acute repetitive seizures and convulsive status epilepticus. Methods This retrospective study included children who received intravenous lacosamide for acute repetitive seizures or convulsive status epilepticus from October 2017 to September 2022 and were admitted to the pediatric intensive care unit at a tertiary medical center. Children who were newly started on intravenous lacosamide were included and divided into two groups: (a) previously healthy, and (b) history of epilepsy and receiving antiseizure medications. Efficacy was defined as the cessation of seizures within 72 h of administering lacosamide. Adverse effects were defined using predefined criteria, and most were evaluated during the first 7 days. Results Sixty‐seven children were enrolled, including 25 (37.3%) girls and 42 (62.7%) boys with a mean age of 7.20 ± 5.66 years. Among them, 30 (44.8%) had acute repetitive seizures, and 37 (55.2%) had convulsive status epilepticus. The seizure types were focal onset (n = 34, 50.7%), generalized onset (n = 27, 40.3%), and mixed type (n = 6, 9.0%). In the previously healthy group, 9 patients had acute repetitive seizures and 23 had convulsive status epilepticus, and the rates of seizure cessation when lacosamide was used as the first to fourth choice of antiseizure medication were 100.0%, 85.7%, 40.0%, and 50.0%, respectively, compared to 73.7%, 54.5%, 100.0%, and 0.0% in the patients with epilepsy (21 had acute repetitive seizures and 14 had convulsive status epilepticus). Sixteen (23.9%) patients developed bradycardia and 1 (1.5%) patient developed a rash. Significance The early use of intravenous lacosamide was effective with acceptable side effects in treating acute repetitive seizures and convulsive status epilepticus in critically ill children, including young infants and children less than 4 years old and those with different etiologies. Plain Language Summary Acute repetitive seizures and convulsive status epilepticus are common neurological emergencies in pediatric intensive care units (PICUs), traditional intravenous antiseizure medications (ASMs) include phenytoin, valproic acid, levetiracetam, and phenobarbital. In this study, we categorized patients based on their epilepsy history and different etiologies. We observed that early use of lacosamide, even in young infants, demonstrated good efficacy and safety.